Modelling of timber joints in traditional structures - Branco, J. (2012)
Original unstrengthened timber connections and the effects of different strengthening techniques have been evaluated experimentally with tests on full-scale birdsmouth joints. Experimental results show that structural response of traditional timber connections under cyclic loading cannot be represented by common constraint models, like perfect hinges or rigid joints, but should be using semi-rigid and friction based models. A research program has investigated the behaviour of old timber joints and examined strengthening criteria. The main parameters affecting the mechanical behaviour of the connection have been singled out. A synthetic model of cyclic behaviour has been adapted on the basis of experimental results.